Improving the Practical Experience of VR Games Based on Custom Gesture Interaction—Taking Minecraft as an Example - Wan, Jinrun (Transactions on Environment, Energy and Earth Sciences, 2026)
Although virtual reality (VR) games have developed rapidly, they still face the problem of low user retention rates due to poor interactive experiences. To address the issues of VR users' immersive experience and the operational efficiency of VR games, this study takes the VR mod Vivecraft of Minecraft as an example and proposes a user-defined gesture system that integrates a shortcut key operation mode and a gesture mapping framework, and demonstrates the feasibility of this solution through the classic operations of "flying in the game" and "reloading in the game" as cases. The research results show that this solution can significantly enhance players' sense of immersion and the operational feel within the game. However, the study also finds that user-defined gestures have problems such as gesture misjudgment, insufficient gesture accuracy, and high development difficulty, which need to be solved with multiple references in the future. This study provides theoretical and practical references for VR gesture interaction design.
Keywords: VR gesture interaction design; Shortcut key; Gesture customization; Minecraft.